2006
DOI: 10.1016/j.rapm.2005.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Critical Failure of a Percutaneous Discectomy Probe Requiring Surgical Removal During Disc Decompression

Abstract: The patient had an uneventful recovery. Manipulation of the auger should be performed in a linear motion as best as possible and under fluoroscopic guidance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 4 publications
0
12
0
Order By: Relevance
“…One serious published complication specific to Dekompressor is that of a case of a broken tip which needed to be surgically removed . Another study showed 3 of 26 patients (12.8%) had transient numbness and paresthesia, which resolved spontaneously after a few days, plus 1 case of a superficial skin infection (3.9%) treated successfully with antibiotics .…”
Section: Resultsmentioning
confidence: 99%
“…One serious published complication specific to Dekompressor is that of a case of a broken tip which needed to be surgically removed . Another study showed 3 of 26 patients (12.8%) had transient numbness and paresthesia, which resolved spontaneously after a few days, plus 1 case of a superficial skin infection (3.9%) treated successfully with antibiotics .…”
Section: Resultsmentioning
confidence: 99%
“…Most of the published literature is on lumbar discectomy complications, such as postoperative wound hematoma, neuronal injury (including postoperative dysethesia), recurrent herniation, postoperative instability, wrong level of exposure, arachnoiditis, infection, incidental durotomy (including its long term sequelae), and pseudomeningoceles 1,2,5,9,18,26,35,[38][39][40]47,49,51,53,54) . In addition, there have been case reports of rare complications after lumbar discectomy, such as development of an arteriovenous fistula, major vessel injury, epidural fibrosis, ureteral injury, compartment syndrome with acute renal failure, iliac artery injury, intradural disc migration, bowel injury, septicemia, symptomatic pneumorachis, instrument failure, postoperative radicular neuroma, Ogilvie's syndrome, and reflex sympathetic dystrophy 3,4,10,12,13,[15][16][17]19,21,22,34,36,37,41,44,45,48,52) . In reports on cases subsequent to full endoscopic discectomy, published complications have included recurrent disc herniation on the same side, incomplete removal of a ruptured disc, infection, neuronal injury (including sensory changes), dural tears, vascular injury, psoas hematoma, and sympathetically mediated pain [6][7][8]11,14,[23][24][25]…”
Section: Discussionmentioning
confidence: 99%
“…Less frequently encountered complications of the technique include reflex sympathetic dystrophy, puncture of thecal sac with accompanying headache, hemorrhage and neurologic injury, allergic reactions to any of the agents used during the procedure, pneumothorax (in case of thoracic intervertebral disc decompression), and vasovagal reactions (in case of cervical intervertebral disc decompression) [13,[23][24][25]29]. In addition, material failure resulting from open surgery has been described [30]. Finally, there is a case of cauda equine syndrome reported by Onik et al due to improperly placed nucleotome, but this was related to an interlaminar approach [31] (Table 1).…”
Section: Complicationsmentioning
confidence: 99%